(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
These methods are carried out in several ways to help prevent the struggle with destructive ideas and disorders through educational support, examination and family cooperation. Good interactions, support, and self-expression for students who encounter such problems are very important.